Antioxidant Potential Of Lansium Domesticum Corr. Seed Extract In White Male Rat (Rattus Novergicus) Induced By Alcohol - Subandrate Subandrate; Sadakata Sinulingga; Sri Wahyuni; M Fakhri Altiyan; Fatmawati Fatmawati (Molekul, 2016)
Lansium domesticum Corr. is a typical plant of Indonesia. The seeds have a lot of useful compounds, such as flavonoids. Flavonoids are a natural compound that can act as antioxidants. The aim of this study was to determine the antioxidant potential of Lansiumdomesticum Corr. seed extract. This study was an experimental research with posttest control group design. The subjects were 32 white male rats. Rats were randomly divided into 4 groups: negative control group was given suspension of Na CMC 1%, dose group I, II and III were given Lansium domesticum Corr. seed extract with each dose of 100mg/kg, 200 mg/kg, and 300 mg/kg. Observation of the subject's response was done by measuring the levels of glutathione (GSH) and malondialdehyde (MDA). Analysis ANOVA test showed that there was a group that had an average difference both GSH levels (p=0.00) and MDA levels (p=0.00). Post hoc test analysis for GSH levels and MDA levels showed that only a dose of 100 mg/kg which have significant differences (p=0.00). Thus, Lansiumdomesticum Corr. seed extract has antioxidant potential and optimum dose of 100 mg/kg.